Psychological and Behavioral Responses in South Korea During the Early Stages of Coronavirus Disease 2019 (COVID-19) - Lee, Minjung; You, Myoungsoon (International journal of environmental research and public health, 2020)
Background: The psychological and behavioral responses during the early stage of Coronavirus disease 2019 (COVID-19) in South Korea were investigated to guide the public as full and active participants of public health emergency preparedness (PHEP), which is essential to improving resilience and reducing the population’s fundamental vulnerability. Methods: Data were collected through an online survey four weeks after the Korea Centers for Disease Control and Prevention (KCDC) confirmed the first case in South Korea; 973 subjects were included in the analysis. Results: Respondents’ perceived risk of COVID-19 infection; the majority of respondents reported that their perceived chance of infection was “neither high nor low” (51.3%). The average perceived severity score was higher than perceived susceptibility; 48.6 % reported that the severity would be “high,” while 19.9% reported “very high.” Many respondents reported taking precautions, 67.8% reported always practicing hand hygiene, and 63.2% reported always wearing a facial mask when outside. Approximately 50% reported postponing or canceling social events, and 41.5% were avoiding crowded places. Practicing precautionary behaviors associated strongly with perceived risk and response efficacy of the behavior. Conclusions: Our study confirmed the significance of the psychological responses, which associated with behavioral responses and significantly influenced the public’s level of public health emergency preparedness regarding the COVID-19 pandemic. This result has consequences not only for implementing public health strategies for the pandemic but also for understanding future emerging infectious diseases.